The impact of informal coach training on the personal development of youth sport athletes - MacDonald, D. J.; Côté, J.; Deakin, J. (International Journal of Sports Science and Coaching, 2010)
The role of adults has been outlined as a critical aspect of positive development of young athletes. Youth-sport coaches interact constantly with athletes and hence have the potential to impact significantly on the experiences of youth. Formal coach training has been proposed as a method for helping coaches interact effectively with athletes, but research shows that many coaches learn through experience and interactions with other coaches. The purpose of this study was to determine if coach training offered through the sport program impacts positively on the personal development of youth. Results suggest that athletes who played for coaches that received training through their program reported higher rates of personal and social skills than athletes who played for untrained coaches. Implications for sport programs' administrators are discussed along with recommendations for incorporating positive development principles within a sport environment.